Different genotypes and species of symbiotic fungi mediate the behavioral response of invasive Sirex noctilio fabricius (Hymenoptera: Siricidae) - Wang, Ming; Gao, ChengLong; Xu, QinWang; Fu, NingNing; Li, JiaLe; Ren, LiLi; Luo, YouQing (Frontiers in Microbiology, 2024)
In northeast China, the invasive woodwasp, Sirex noctilio, attacks Pinus sylvestris var. mongolica Litv and often shares habitat with native Sirex nitobei. Previous research showed that S. noctilio can utilize the volatiles from its symbiotic fungus (A. areolatum IGS-BD) to locate host trees. Consequently, symbiotic fungi (A. areolatum IGS-D and A. chailletii) carried by S. nitobei may influence the behavioral selection of S. noctilio. This study aimed sought to investigate the impact of fungal odor sources on S. noctilio's behavior in laboratory and field experiments. Our observations revealed that female woodwasps exhibited greater attraction towards the fungal volaties of 14 -dayold Amylostereum IGS-D in a "Y"-tube olfactometer and wind tunnel. When woodwasps were released into bolts inoculated separately with three strains in the field, females of S. noctilio exhibited a preference for those bolts pre-inoculated with A. areolatum IGS-BD. GC-MS analysis revealed that the volatiles emitted by the two genetypes of A. areolatum were similar, yet significantly distinct from those of A. chailletii. Hence, we postulate that the existence of native A. areolatum IGS-D could potentially facilitate the colonization of S. noctilio in scenarios with minimal or no A. areolatum IGS-BD present in the host. 1 Introduction fungal 删除[ming]: Background: 删除[ming]: se 删除[ming]: volatiles 删除[ming]: sel 删除[ming]: ect the potential 删除[ming]: Different genotypes and species of fungal 删除[ming]: e 删除[ming]: determine 删除[ming]: extent 删除[ming]: to which the odor source affects 删除[ming]: Results: 删除[ming]: were attracted to 删除[ming]: ( 删除[ming]: ) 删除[ming]: of both 删除[ming]: species. 删除[ming]: The genotypes of symbiotic fungi have certain effects on the oviposite behavior of S. noctilio. Sirex noctilio 删除[ming]: the invasive 删除[ming]: , which may be a strategy to improve the fitness of S. noctilio 删除[ming]: The volatiles of 删除[ming]: 删除[ming]: and the synergistic interaction with host volatiles 删除[ming]: may be beneficial to 删除[ming]: the invasive 删除[ming]:. Conclusion: Based on the responses of females to the fungal strains, the invasive S. noctilio would partly use